2014
DOI: 10.1002/cncr.28865
|View full text |Cite
|
Sign up to set email alerts
|

Postmastectomy radiation therapy for T3N0: A SEER analysis

Abstract: Background There is conflicting evidence regarding the benefit of post-mastectomy radiation therapy (PMRT) for pathologic stage T3N0M0 breast cancers. We analyzed data from the Surveillance, Epidemiology, and End Results (SEER) database to investigate the benefit of PMRT in these patients. Methods We queried the SEER database for T3N0M0 breast cancer patients diagnosed from 2000–2010 who underwent modified radical mastectomy. We excluded males, patients with unknown radiation timing/type, other primary tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 14 publications
1
23
2
Order By: Relevance
“…Our data are in contrast to an updated SEER analysis of T3N0M0 from the years 2000e2010 by Johnson et al [14]. This study included 2525 patients and noted an improvement in breast cancer-specific survival in patients undergoing PMRT (85.0 versus 82.4%, P < 0.01).…”
Section: Discussioncontrasting
confidence: 93%
“…Our data are in contrast to an updated SEER analysis of T3N0M0 from the years 2000e2010 by Johnson et al [14]. This study included 2525 patients and noted an improvement in breast cancer-specific survival in patients undergoing PMRT (85.0 versus 82.4%, P < 0.01).…”
Section: Discussioncontrasting
confidence: 93%
“…Because approximately 33% of patients treated with PMRT also received RNI in addition to chest wall RT, we also were able to examine the role of RNI in patients with pT3N0 breast cancer. 9 Several additional single institutional studies also have found a benefit for PMRT. Previous prospective and retrospective studies also have shown that PMRT improves OS in women with pT3N0 breast cancer.…”
Section: Discussionmentioning
confidence: 97%
“…1 Although the overall incidence of breast cancer is high, the number of large primary breast malignancies without lymph node involvement is small because the risk of lymph node disease generally increases with tumor size. [5][6][7][8][9][10][11] Therefore, very few patients with T3N0 disease have received treatment as part of a randomized trial examining postmastectomy radiotherapy (PMRT). [5][6][7][8][9][10][11] Therefore, very few patients with T3N0 disease have received treatment as part of a randomized trial examining postmastectomy radiotherapy (PMRT).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple additional studies have been conducted using the Surveillance, Epidemiology, and End Results database, with mixed results. The most recent analysis demonstrated improvements in both cancer‐specific survival and overall survival with PMRT …”
Section: Introductionmentioning
confidence: 99%